Effects of simulated time delay on teleoperators' performance in inter-urban conditions. (January 2023) - Musicant, Oren; Botzer, Assaf; Shoval, Shraga
Highlights: Teleoperation of vehicles has safety and economic benefits. Time delay in the cellular network is a key challenge for safe teleoperation. Effects of small delays on performance in simulated inter-urban scenarios were tested. A 250 ms delay significantly impinged on performance relative to a 50 ms delay. Policy makers should consider that even small delays matter. Abstract: Time delay in communication networks is a major challenge in controlling vehicles from remote centers (also known as teleoperation). In the current study, we investigated the effects of time delay in controlled and partly controlled driving environments at higher driving speeds and in relatively short time delays (50 ms, 150 ms, and 250 ms) which characterise the 5G era. Participants (N = 72) faced several challenges while operating a vehicle in a simulated scenario. The challenges started with following a lead vehicle on a curve, continued with responding to a sudden brake of the lead vehicle, and concluded with highway driving among other simulated road users. The speed, the distance to other vehicles, the brake and swerving of the vehicle and the crash rate were measured during each scenario. At the end of the scenario, participants completed the NASA-TLX. We found that at a time delay of 250 ms (but not 150 ms), following a lead vehicle on a curved road was characterized by a higher standard deviation of speed and distance to the lead vehicle and stronger swerving than at the shorter time delay of 50 ms. Swerving was also stronger at the 250 ms than at the 50 ms delay on the highway. Finally, crashes, which occurred mainly on the highway and in response to the sudden brake of the lead vehicle (before the highway), were 20 % (not statistically significant) higher at the 250 ms than at the 50 ms delay. The gap in collision frequency between the 150 ms and 50 ms delay was lower (8 %) and not statistically significant. This relatively small gap corresponded with the insignificant changes between 150 ms and 50 ms delay on the other indices of driving safety that we analyzed (e.g., braking and swerving). Regarding the NASA-TLX, participants rated the 250 ms delay higher than the other delays on almost all dimensions except for effort on which they did not distinguish between the 250 ms and the 150 ms delay. Our findings expand current knowledge on the effects of time delay on teleoperation. In the Discussion section, we translate this knowledge into practical recommendations regarding possible delays in teleoperation and possible countermeasures for the time delay.